THE INFLUENCE OF DEMOGRAPHY, SOCIAL MEDIA, RISK ATTITUDE, AND OVERCONFIDENCE ON THE FINANCIAL LITERACY OF USERS SOCIAL MEDIA IN SURABAYA - Rizon Rizon; Njo Anastasia; Evelyn Evelyn (Finance and Investment Program, School of Business and Management - Petra Christian University, 2021)
This study aims to examine the influence of demography, social media, risk attitude, and overconfidence on the financial literacy of users of social media in Surabaya. The sample used in this study amounted to 300 respondents. Data were collected using a online questionnaire via Google Form. The data analysis method used in this study is PLS. The analysis test results show that there is an effect of demography, social media, risk attitude, and overconfidence on users' financial literacy in Surabaya.